EFFECT OF SOME PARAMETERS ON THE PRODUCTION OF RIFAMYCINS BAND SV BY AMYCOLATOPSIS MEDITERRANEI (Biological Sciences - PJSIR, 2022)
The effect of different parameters on the production of rifamycins Band SV were studied. The optimum productionwas obtained after four days. The concentration ratio of starch to glucose at 20: 10 g/L was favourable for theantibiotic production. The effect of nitrogen compounds indicated that the phenylenediamine, potassium phthalimideand uracil have a stimulating effect on the production of rifamycin B by Amycolatopsis mediterranei similar to thebarbital; specially uracil at 2 g/L.